2016
DOI: 10.1371/journal.pone.0146892
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality Predicts Poor Medication Adherence in Chinese Patients with Type 2 Diabetes Mellitus: A Six-Month Follow-Up Study

Abstract: BackgroundType D personality and medication nonadherence have been shown to be associated with poor health outcomes. Type D personality is associated with poor medication adherence in patients with coronary artery disease, myocardial infarction, and heart failure. However, the relationship between type D personality and medication adherence in patients with Type 2 Diabetes Mellitus (T2DM) remains unknown. This study aims to examine whether type D personality was associated with medication adherence in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 76 publications
2
51
1
Order By: Relevance
“…One study found that in‐patients with myocardial infarction and depression, type D personality, which is characterized by negative affect and social inhibition, is more common in prior depression compared to new‐onset depression after myocardial infarction . People with this personality trait have been reported to have increased cardiac mortality , while they also experience delayed diagnosis for somatic diseases and have poor medical compliance . This may also partly explain our findings.…”
Section: Discussionmentioning
confidence: 72%
“…One study found that in‐patients with myocardial infarction and depression, type D personality, which is characterized by negative affect and social inhibition, is more common in prior depression compared to new‐onset depression after myocardial infarction . People with this personality trait have been reported to have increased cardiac mortality , while they also experience delayed diagnosis for somatic diseases and have poor medical compliance . This may also partly explain our findings.…”
Section: Discussionmentioning
confidence: 72%
“…Milicevic et al22 found that T2DM patients with Type D personality were less compliant with visits to primary care physicians. Li et al23 discovered that Type D personality predicted poor medication adherence in T2DM patients. More studies are needed to understand the impact of Type D personality in relation to other important sociopsychological factors in T2DM patients, such as self-efficacy and social support.…”
Section: Introductionmentioning
confidence: 99%
“…This study found type D personality has an inverse association with self-care behavior. Likewise, the report stated that patients with type D personality significantly have low medication adherence (Li et al, 2016). Another study showed that patients with type D personality tend to have lower levels of medication self-efficacy and medication adherence than others (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 98%